Decorative Translation: A Translation Strategy Falling Between ‘Foreignization’ and ‘Domestication’ - Ma, Hanyi (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2020)
This dissertation aims to argue that there is a third option between ‘foreignization’ and ‘domestication’ by suggesting the experimental methodology ‘decorative translation’. The new strategy will combine the features of both the source and target language traditions. I will create a converter that transfers the source characters into target words, and will use other additional methods, in-sentence explicitation and spreading information, to help complete the new strategy. Meanwhile, a test translation of yi shou zhi (异兽志), Journal of Fantastic Beasts will be done applying ‘decorative translation’. By doing so, the merits and the drawbacks of the methodology will be shown and analysed. The success of the strategy will be assessed with a readers’ report. The readers’ report will be created with Google Forms based on the contents of the test translation and will be sent to readers via emails. Definitions of ‘foreignization’ and ‘domestication’ will be given in this paper, with a brief discussion of the concepts that are brought up by various translation theorists, such as Friedrich Schleiermacher, Antoine Berman and Lawrence Venuti. The new strategy will attempt to compensate for deficiencies in their theories.
Keywords: Literary Translation